Bed Nucleus of the Stria Terminalis GABA neurons are necessary for changes in foraging behavior following an innate threat - Ly, Annie; Barker, Alexandra; Prévost, Emily D; McGovern, Dillon J; Kilpatrick, Zachary; Root, David H (bioRxiv, 2023)
Foraging is a universal behavior that has co-evolved with predation pressure. We investigated the role of bed nucleus of the stria terminalis (BNST) GABA neurons in robotic and live predator threat processing and their consequences in post-threat encounter foraging. Mice were trained to procure food in a laboratory-based foraging apparatus in which food pellets were placed at discrete and incrementally greater distances from a nest zone. After mice learned to forage, they were exposed to either a robotic or live predator threat, while BNST GABA neurons were chemogenetically inhibited. Post-robotic threat encounter, mice spent more time in the nest zone, but other foraging parameters were unchanged compared to pre-encounter behavior. Inhibition of BNST GABA neurons had no effect on foraging behavior post-robotic threat encounter. Following live predator exposure, control mice spent significantly more time in the nest zone, increased their latency to successfully forage, and their overall foraging performance was significantly a ltered. I nhibition o f BNST GABA neurons during live predator exposure prevented changes in foraging behavior from developing after live predator threat. BNST GABA neuron inhibition did not alter foraging behavior during robotic or live predator threat. We conclude that while both robotic and live predator encounter effectively intrude on foraging behavior, the perceived risk and behavioral consequence of the threats are distinguishable. Additionally, BNST GABA neurons may play a role in the integration of prior innate predator threat experience that results in hypervigilance during post-encounter foraging behavior.